FINANCIAL FACTORS INFLUENCE ON TAX AGGRESSIVENESS (Study on Indonesian Consumption Sectors 2018-2020) - Gabriel Nadya Amarissa; Nofri Nautani; Mansur Yal Harist; Chandra Rony Lumbantobing (Kesatuan Press, 2023)
Taxes, viewed from the government's point of view, are the largest source of revenue. Such a significant contribution to the state makes the government pays more attention and create more effort to optimize tax revenue. However, from the company's viewpoint, tax payments are considered as costs and affect them by reducing their profits. Therefore, the differences in perspective between the government and the corporations will result in companies neglecting to pay taxes. This study analyzes the effect of profitability, company size, and capital intensity on tax aggressiveness listed on the Indonesian Stock Exchange in 2018-2020. This research uses multiple linear regression analysis with quantitative methods and uses purposive sampling as a sampling method. The research data used are in the form of financial statements of manufacturing companies in the consumption sector that have undergone an audit and publication process. The result of this study indicates that profitability harms tax aggressiveness, company size affects tax aggressiveness, capital intensity has no effect on tax aggressiveness, and profitability, company size, and capital intensity have a simultaneous effect on tax aggressiveness.